Skeletal muscle adaptations underlying performance-enhancing effects of high-intensity interval training - Fiorenza, M. (8th International Congress Mountain Sport & Health. Updating Study and Research from Laboratory to Field. 7-8 November 2019, Rovereto (TN) - Italy. Programme and Book of Abstracts, 2019)
In recent years, high-intensity interval training (HIIT) has received considerable attention from the scientific community owing to its effectiveness in enhancing exercise performance and improving cardiovascular and metabolic health. HIIT promotes a number of adaptations resembling those associated with traditional endurance exercise, including quantitative and qualitative changes at the skeletal muscle mitochondrial level. However, the mechanisms underlying these similar adaptive responses in spite of divergent exercise stimuli are not completely clear. Hence, we explored the acute effects of different exercise stimuli on muscle metabolism and the molecular cascade promoting mitochondrial adaptations; an experimental approach that allowed us to gain insights into the events that initiate the hormetic process leading to increased muscle oxidative capacity. Thereafter, we investigated the long-term effects of HIIT on muscle mitochondrial function and exercise performance. I will present results from these studies and others that suggest a prominent role of skeletal muscle mitochondria in the performance-enhancing effects of HIIT.